Congenital lateral cervical fistulas derived from the first branchial groove: about an observation - Varela, Nelson B; Gateño Yaffe, Nisso J (Cirugía del Uruguay, 2021)
A report is made of an infrequent case of congenital cervical fistula arising from the first branchial cleft. Considerations about embriology, pathology and clinic of this infrequent affection are made.